2010
DOI: 10.1177/008124631004000204
|View full text |Cite
|
Sign up to set email alerts
|

Secondary Traumatic Stress, Level of Exposure, Empathy and Social Support in Trauma Workers

Abstract: In South Africa the incidence of violent crime is an everyday occurrence that affects the majority of the population directly and/or indirectly. Research reveals that counselling victims of violent crime may cause psychological symptoms in trauma workers, which in turn may lead to Secondary Traumatic Stress (STS). However, despite this knowledge, there appear to be very fewtrauma studies that focus on trauma workers. Furthermore there also appears to be a lack of studies that focus on the roles that key variab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
83
5
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(95 citation statements)
references
References 11 publications
2
83
5
5
Order By: Relevance
“…Given the robust and convincing data indicating the association of multiple ACEs with negative health, mental health, and quality-of-life outcomes, and research suggesting that prior trauma increases the risk for later retraumatization (MacRitchie & Leibowitz, 2010) and may compromise effective practice for human service professionals, these outcomes warrant further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Given the robust and convincing data indicating the association of multiple ACEs with negative health, mental health, and quality-of-life outcomes, and research suggesting that prior trauma increases the risk for later retraumatization (MacRitchie & Leibowitz, 2010) and may compromise effective practice for human service professionals, these outcomes warrant further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…However, Empathy was investigated in the literature and few studies found connection between empathy and STS. A study by MacRitchie, and Leibowitz investigated the relationship between level of shared empathy and STS among 64 trauma workers, and reported that empathy is a significant moderator between exposure to traumatic events and STS development [39]. This connection was sustained by Sheen et al who reported that empathy was identified as a risk factor for STS in both quantitative and qualitative literature [40].…”
Section: Personal Factorsmentioning
confidence: 99%
“…As discussed earlier, the crime rate in the country is high and a large number of people are victims of crime. Citizens do not feel safe (Louw, 2007) and being victims of crime and daily reminders of incidences of crime by the media contribute to feelings of traumatisation (Wardrop, 2009;MacRitchie & Leibowitz, 2010). Zastrow (2012, p. 45) refers to the ecological approach that conceptualises 'dysfunctional transactions between people and their social and physical environments'.…”
Section: Resultsmentioning
confidence: 99%
“…Offenders and specifically sex offenders may be regarded with fear and disgust (MacRitchie & Leibowitz, 2010;Olver & Barlow, 2010), often aggravated by the sensational media portrayal of offending, prisons and victims (Scott et al, 2006;Varma, 2006). Scott et al (2006) also mention attitudes about race as a factor that contributes to fear of youth offenders.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation